Enhancing Product UpgradaProduct Modular Enhancement Framework (PMEF): A New Approach to Product Upgradationtion: A Study on theModular Enhancement Framework (MEF) (International Journal of Scientific Research and Management (IJSRM), 2025)
Background In today’s rapidly evolving and highly competitive market, the ability to upgrade existing products is essential for companies to maintain their market position and meet changing customer needs. By discovering new methods, we can implement changes more swiftly and with fewer resources, minimizing the risk of widespread issues and ensuring that upgrades are more manageable. Objective The objective is to develop a simple product enhancement framework for product upgradation. This framework aims to offer greater flexibility, faster implementation, and efficient resource allocation, making it an attractive option for companies looking to enhance their product offerings. Methods An analysis was conducted on the data provided by leading manufacturers worldwide regarding their recent product upgrades. This analysis encom- passed the product upgradation process, the outcomes of these upgrades, market research reports, competitor analysis, customer feedback, and internal company documents. From the data gathered, we identified gaps in the product upgradation process and the reasons for failures, leading to the development of a universal framework. Results The proposed Product Modular Enhancement Framework (PMEF) provides notable benefits in terms of flexibility, efficiency, and scalability. Its modular structure allows for independent upgrades, minimizing the risk of widespread issues and facilitating quicker implementation. Conclusion The PMEF represents a promising approach to product upgradation, offering a structured and innovative solution to meet the demands of a dynamic market. While the framework presents several benefits, it also requires meticulous planning and execution to address challenges such as module integration and resource allocation.